Investigating teaching practices in large classes: A case study of public primary schools in Tanzania - Issa, Hidaya Mohammed; Castulo, Nilo Jayoma (Journal of Interdisciplinary Studies in Education, 2026)
This study explores primary school teachers’ professional experiences in managing large classes, focusing on their characteristics, teaching and assessment practices, and the challenges they face. A critical case study approach using Atlas.ti 24, with semistructured interviews of 12 teachers (six male and six female) from two primary schools in Tanzania, was employed. Teachers developed their nurturing characteristics over time when teaching large classes. Teachers rely primarily on teacher-centered methods, such as lectures, corporal punishment discipline, and note-taking. Assessment practices include group tasks and summative tests; however, individualized assessments remain a challenge. Teachers face significant challenges, including insufficient resources, poor classroom environments, and limited government support. The small sample size limits the study’s generalizability.